Carbon ion radiotherapy as definitive treatment in locally recurrent pancreatic cancer - Liermann, Jakob; Ben-Josef, Edgar; Syed, Mustafa; Debus, Jürgen; Herfarth, Klaus; Naumann, Patrick (Strahlentherapie und Onkologie, 2022)
Data on management of locally recurrent pancreatic cancer (LRPC) after primary resection are limited. Recently, surprisingly high overall survival rates were reported after irradiation with carbon ions. Here, we report on our clinical experience using carbon ion radiotherapy as definitive treatment in LRPC at the Heidelberg Ion-Beam Therapy Center (HIT).